Determine all possible triplet(s) (E, F, G) of positive integers, with E and F being prime numbers and E ≥ F, that satisfy this equation:
E-1 + F-1 + (E*F) -1 = G-1
(In reply to
analytical solution by Daniel)
Bravo Daniel, I came to the same conclusion once my computer had found only the one triple.
My belated proof starts off like yours as far as E + F + 1 = EF
then I rearrange to get EF - E - F + 1 = 2
in order to factorise (E - 1)(F - 1) = 2
Since E & F are integers with E >= F > 0, E - 1 = 2 and F - 1 = 1, giving the triple (3, 2, 1) as the only solution.
|
Posted by Harry
on 2009-07-18 21:09:53 |